EFEKTIVITAS TEKNIK MNEMONIK TIPE AKROSTIK DALAM PEMBELAJARAN AFIKSASI BAHASA INDONESIA - Wahyudi, Wahyudi; Saman, Sisilya; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe complex and many information in the linguistic rules of the Bahasa subject in curriculum 2013 makes students difficult to memorize. Especially in affixation material that has no abstract and meaning. This study aims to describe the application of mnemonic techniques accrostic type to improve memory in language affixation learning of Bahasa on grade X IPS SMAN 3 Pontianak. The research design used was experimental type with quantitative. The subjects of the research are the students of class X IPS 1 as experiment class and X IPS 3 as control class. While the value of the average pre-test of the experimental group students was 47,39 and the posttest average score is 84,12. Calculation of significant differences in the experimental group is 13,15. The magnitude of the influence of the use of accrostic-typemnemonik techniques have been calculated which is obtained ES of 1,17 > 0,8 which included in the high criteria. It is concluded that the use of accrostic-type mnemonic techniques has a significant effect on students’ memory level. Keywords: effectiveness, mnemonics, accrostic, affixation.